Sources of Salmonella Infections in Selected Poultry Farms in Jos, Northern Nigeria - Sati, N. M.; Emennaa, P. E; Okolocha, E. C. (Journal of Advances in Microbiology, 2020)
Salmonella infections are not new in Nigerian farms and most times also, it is not clear whether the infections are coming from the hatcheries or they are acquired on the farms. The aim of this study was to determine the sources of salmonella infections in nine selected farms prior to fowl typhoid vaccine administration in order to suggest preventive measures towards minimizing or eradicating its occurrence in the farms and hatcheries. Samples taken at the hatcheries were dead chicks and faeces from chick boxes. These samples were processed and analysed for Salmonella species using standard microbiology methods. Four (44.4%) of the nine farms had Salmonella in the tissues of dead birds and/or in their faeces before the birds were introduced to the farms. Salmonella specie was also found two weeks later in faeces and feed in one out of the four farms. Subsequent visits yielded no Salmonella species in the previously infected farms. One of the selected farms whose chicks were Salmonella–free before reaching the farm eventually had Salmonella species isolated from the litter a few weeks later. A total of eleven isolates comprising four different serotypes (Salmonella oakland, S. enterica subsp enterica, S. bonariensis and S. kentucky) were encountered in this study that demonstrates the need for routine screening of breeder farms against infectious diseases, the regulation of activities in hatcheries and the practice of biosecurity on farms to reduce disease transmission to the barest minimum.
Keywords: Salmonella; sources; infection; poultry farm; Ahmadu Bello University; ACENTDFB; J. Kabir; H. M. Kazeem